2016
DOI: 10.1002/jbm.a.35932
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vivo performance of nitric oxide‐releasing extracorporeal circuits in a feline model of thrombogenicity

Abstract: Infection and thrombosis are the two leading complications associated with blood contacting medical devices, and have led to the development of active materials that can delivery antibiotics or antithrombotic agents. Two key characteristics of these materials are the ability to produce controlled delivery, as well as minimal systemic delivery of the agent outside of the device site. Nitric oxide (NO) releasing materials are attractive as NO plays pivotal roles in the body's natural defense against bacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…The partly penetrated morphology of S1 crystals into the grafts, which illustrate a possible firm attachment within SDVG bulk, can explain the same period of NO‐release from this structure compared with S2 crystals while the crystals were smaller in size compared to S2 crystals. It was reported in other studies that the long‐term release of NO is related to crystal stability within the polymer matrix which is in agreement with the results of NO‐release in the current study (Goudie, Brainard, et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The partly penetrated morphology of S1 crystals into the grafts, which illustrate a possible firm attachment within SDVG bulk, can explain the same period of NO‐release from this structure compared with S2 crystals while the crystals were smaller in size compared to S2 crystals. It was reported in other studies that the long‐term release of NO is related to crystal stability within the polymer matrix which is in agreement with the results of NO‐release in the current study (Goudie, Brainard, et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the S1 crystals were dispersed more homogeneously and are in a broader range of sizes while the S2‐impregnated crystals are more similar in size. This microscale roughness of PLA after S2 impregnation is consistent with previous reports (Goudie, Brainard, Schmiedt, & Handa, ).…”
Section: Resultssupporting
confidence: 92%
“…Water contact angles of control CarboSil, SNAP CarboSil, BPAM CarboSil, and SNAP-BPAM CarboSil surfaces are listed in Table 1. We have previously shown that due to lower water uptake of CarboSil, limited leaching of SNAP has been seen from SNAP doped CarboSil [71]. The study showed that leaching is further reduced with the use of a top coat as compared to the non-coated films.…”
Section: Resultsmentioning
confidence: 98%
“…Incorporation of SNAP to CarboSil has shown to provide continuous and localized NO delivery to specific sites of interest [70, 71]. The incorporation of SNAP in medical grade polymers have been shown to be hemocompatible and possesses stability during long-term storage at room temperature and physiological conditions [63, 72, 73].…”
Section: Resultsmentioning
confidence: 99%
“…Nitric oxide (NO) is an endogenous gas that is released from the natural endothelium and is proven to be a strong antimicrobial agent (Brisbois et al, 2015; Brisbois, Major, Goudie, Bartlett et al, 2016; Sundaram, Pant, Goudie, Mani, & Handa, 2016). NO has a number of other biological function such as vasodilation, thrombosis, and aids in wound healing (Brisbois et al, 2015; Brisbois, Major, Goudie, Meyerhoff et al, 2016; Goudie, Brainard, Schmiedt, & Handa, 2017; Goudie et al, 2016). More specifically, NO that is released in the sinus cavities and by neutrophils and macrophages functions as an effective natural antiseptic agent (Brisbois et al, 2015; Degano, Genestal, Serrano, Rami, & Arnal, 2005).…”
Section: Introductionmentioning
confidence: 99%